Evaluation of Smart Charity Possibilities in Developing Countries Based on Web3 Trends: Non-Fungible Tokens (NFT) and Smart Contracts Introduction - Dmitry Mikhaylov; Evgeny Xata; Abubakar Khamchiev (Research Synergy Foundation, 2024)
The role of Web3 technologies was examined specifically regarding SmartCharity and their effect on the financing and delivery of public goods in developing countries. The research focused on the case of SmartCharity, its role in making fund distribution more transparent and efficient, and the role of NFTs and smart contracts’ efficacy in changing. For primary data, the cross-sectional study used interviews and questionnaires administered to the critical actors in or close to SmartCharity initiatives; secondary data came from project reports and publicly accessible sources. Quantitative analysis uses statistics to identify trends and correlations in data, whereas qualitative data analysis identifies such trends and patterns. This paper aimed to establish an appreciation of the strengths and weaknesses of Web3 innovation in public good management and make future suggestions for improvement.